PENGEMBANGAN MEDIA PEMBELAJARAN ARTSTEPS UNTUK MENINGKATKAN HASIL BELAJAR SENI MUSIK: Materi Alat Musik Tradisional Siswa Kelas IV SD - Mukti, Ringgar Wahyu Tri; Fathurrahman, Moh. Fathurrahman (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
In today's times, traditional musical instruments need to be preserved because young people today are less concerned with the existence of authentic Indonesian culture. The preservation of Indonesian culture, especially regional musical instruments, can be done during learning in elementary schools. In line with this, teachers need to keep up with the times in the learning process. This study aims to develop learning media based on the artsteps application and test its feasibility and effectiveness. This research uses the Research and Development (R&D) method with the Borg and Gall model using 8 stages including: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) initial trial (small scale); (7) product revision; (8) trial usage (large scale). The results of the development of learning media based on the artsteps application get a media expert validation score of 91% and material expert validation of 95.8% and get effectiveness results with an N-Gain percentage of 70.2%, indicating that learning media products based on artsteps applications are feasible and effective to use. Keywords: Artsteps, Learning Media,  Traditional Musical Instruments